2022
DOI: 10.1093/heapol/czac072
|View full text |Cite
|
Sign up to set email alerts
|

The role of community health worker-based care in post-conflict settings: a systematic review

Abstract: Countries affected by conflict often experience the deterioration of health system infrastructure and weakened service delivery. Evidence suggests that healthcare services that leverage local community dynamics may ameliorate health system-related challenges, however, little is known about implementing these interventions in contexts where formal delivery of care is hampered subsequent to conflict. We reviewed the evidence on community health worker (CHW)-delivered healthcare in conflict-affected settings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Hence, CHWs can not only play an important service delivery role, but can also facilitate access to health services' to communities in times of crisis, where such access may otherwise be hampered by mistrust, lack of communication and other barriers. Internationally, the important role that CHWs can play in health crises and pandemics is increasingly being recognised 28,29 . In a recent international review of the role CHWs can play in post‐conflict settings, Werner et al found “four key functions of CHWs in healthcare delivery in post‐conflict settings including (1) access to care and treatment coverage, (2) case management and adherence support, (3) disease detection and monitoring and (4) scaling up of services” 29 (p267) – the latter through facilitating access to services and through task shifting and task sharing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, CHWs can not only play an important service delivery role, but can also facilitate access to health services' to communities in times of crisis, where such access may otherwise be hampered by mistrust, lack of communication and other barriers. Internationally, the important role that CHWs can play in health crises and pandemics is increasingly being recognised 28,29 . In a recent international review of the role CHWs can play in post‐conflict settings, Werner et al found “four key functions of CHWs in healthcare delivery in post‐conflict settings including (1) access to care and treatment coverage, (2) case management and adherence support, (3) disease detection and monitoring and (4) scaling up of services” 29 (p267) – the latter through facilitating access to services and through task shifting and task sharing.…”
Section: Resultsmentioning
confidence: 99%
“…Internationally, the important role that CHWs can play in health crises and pandemics is increasingly being recognised 28,29 . In a recent international review of the role CHWs can play in post‐conflict settings, Werner et al found “four key functions of CHWs in healthcare delivery in post‐conflict settings including (1) access to care and treatment coverage, (2) case management and adherence support, (3) disease detection and monitoring and (4) scaling up of services” 29 (p267) – the latter through facilitating access to services and through task shifting and task sharing. However, more systematic research and policy action is needed to better understand the role CHWs have been playing and can play during health emergencies and in rebuilding health systems after conflicts, both globally and in the Eastern Mediterranean Region, and to advance policy solutions that support their roles.…”
Section: Resultsmentioning
confidence: 99%
“…The present study shows that using the ComPAS simplified protocol and adding CHWs as treatment providers outside health facilities in emergency settings can effectively improve SAM coverage while maintaining effectiveness and reducing expenditures on nutritional intrants. A recent systematic review of post-conflict situations stated that in contexts with high disease burdens and weak infrastructure, CHWs are key actors in increasing access to basic healthcare ( 58 ). The present study showed a significant increase in SAM coverage in the groups that incorporated CHWs.…”
Section: Discussionmentioning
confidence: 99%
“…Their clinical prediction score has the potential to significantly improve Ebola screening procedures in resource‐limited environments that may lack laboratory facilities. Finally, the systematic review by Werner et al 39 . systematic review demonstrated that community health workers can improve health outcomes in postconflict settings by providing essential health care services to difficult‐to‐reach populations.…”
Section: Discussionmentioning
confidence: 99%